An Unusual Cause of Biliary Obstruction - Yeoh, Sern Wei (Libertas Academica, 2012)
Portal biliary ductopathy (PBD) is a condition in which biliary and pancreatic ducts are extrinsically compressed by collateral branches of the portal venous system, which in turn have become dilated and varicosed due to portal hypertension. While the majority of patients with PBD are asymptomatic, a minority can present with symptoms of biliary obstruction and cholangitis with the potential of developing secondary chronic liver disease. This paper reports the case of a 29 year old male presenting with acute cholangitis, in whom PBD was diagnosed radiologically. A brief review of current literature regarding the diagnosis and management of this condition will also be presented.